Transformasi Pos Lintas Batas Negara (PLBN) Terpadu Laut sebagai Simpul Konektivitas Strategis dalam Kerangka BIMP-EAGA Vision 2035 - Fredi Mainassy; Eva Lisantri; Sulviyani Suardi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The BIMP-EAGA Vision 2035 (BEV 2035) marks a significant paradigm shift in border management in Southeast Asia, with a primary focus on integrating a more inclusive, open, harmonized, and resilient system. In this context, sea-based border crossing posts (PLBN) in Indonesia, such as the Sebatik PLBN, the Serasan PLBN, and the Miangas and Marore Border Crossing Stations (BCS), play a strategic role as maritime connectivity nodes connecting Indonesia with neighboring countries. The transformation of these PLBNs faces several challenges, particularly related to the disharmony of CIQS (Customs, Immigration, Quarantine, and Security) regulations between countries, technical obstacles related to non-conventional vessels (NCSS), and inadequate port infrastructure. To overcome these obstacles, strategic measures are needed, such as revising cross-border trade agreements, increasing quarantine capacity and facilities, and strengthening maritime logistics networks between countries. Furthermore, the development of a sustainable blue economy in border areas is crucial to ensure that the PLBN functions not only as an administrative checkpoint but also as a key facilitator in driving economic growth based on maritime resources. Within the framework of the BIMP-EAGA Vision 2035, the Integrated Maritime PLBN is expected to reduce dependence on informal trade and improve the quality of life of border communities by accelerating connectivity, developing the maritime economic sector, and opening international market access for local products. Thus, the PLBN must transform into a catalyst for inclusive and environmentally friendly economic development in Indonesia's border regions.